Sorption of ethanedinitrile in fumigated commodities and its impact on efficacy for Rhyzopertha dominica (Coleoptera: Bostrichidae) and Lasioderma serricorne, (Coleoptera: Anobiidae) control. (March 2020) - Ramadan, Gomaa R.M.; Abdelgaleil, Samir A.M.; Shawir, Mohamed S.; El-bakary, Ahmed S.; Edde, Peter A.; Phillips, Thomas W.
Abstract: The present study evaluated sorption and desorption of ethanedinitrile (EDN) by different agricultural commodities at 2.6 and 4.8 mg/L during a 24 h fumigation period at 25 Cº. This study also investigated the impact of EDN sorption on the toxic efficacy against the lesser grain borer, Rhyzopertha dominica, and the cigarette beetle, Lasioderma serricorne . Results showed that decrease in the free-headspace concentration of EDN was high in all tested commodities. The concentrations of EDN declined by average levels of 99.8, 98.9, 98.5, 96.2 and 84.3% of the initial applied doses for wheat flour, wheat kernels, pinto beans, corn and tobacco leaves, respectively, at both doses by the end of the 24 h exposure periods. The relationship between the decrease in the free-headspace of EDN concentration over time followed the first order kinetics equation which was described as Ct = 1.77e −0.183t, Ct = 0.22e −0.215t, Ct = 2.03e −0.169t, Ct = 2.59e −0.136t, Ct = 2.17e −0.071 at 2.6 mg/L and Ct = 3.32e −0.179t, Ct = 0.41e −0.222t, Ct = 3.55e- 0.165t, Ct = 4.42e 0.14t, Ct = 3.87e 0.071t at 4.8 mg/L for wheat kernels, wheat flour, pinto beans, corn and tobacco leaves, respectively. Moreover, we found that sorption of EDN (mg EDN/kg of commodity) by wheat flour, wheat kernels, pinto beans, corn and tobacco leaves was 12.84, 12.57, 12.66, 12.17 and 37.52 mg/kg at 2.6 mg/L, and 23.73, 22.74, 23.33, 22.73 and 69.37 mg/kg at 4.8 mg/L indicating that more than 99.0, 97.0, 98.0, 96.0 and 90.0% of the initial applied doses were sorbed, respectively. Desorption of EDN from the treated commodities after 1 h aeration and during 1 week of observation was very low, ranging from less than 0.016 mg/L for pinto beans to 0.002 mg/L for wheat flour at day 1. Results also showed that sorption of EDN by wheat kernels or wheat flour led to reductions in the insecticidal activity against L. serricorne and R. dominica mixed life stages cultures. Highlights: Ethanedinitrile, EDN, is a fumigant suspected to have reduced activity due to sorption on agricultural commodities. EDN applied at two doses declined by 99.8 for wheat flour and 84.3% for tobacco leaves. Desorption of EDN from the treated commodities was very low, ranging from less than 0.016 mg/L for pinto beans to 0.002 mg/L for wheat flour at day 1. Sorption of EDN led to reductions in the insecticidal activity against L. serricorne and R. dominica mixed life stages cultures.